2022
DOI: 10.3390/ijerph19159744
|View full text |Cite
|
Sign up to set email alerts
|

Anabasine and Anatabine Exposure Attributable to Cigarette Smoking: National Health and Nutrition Examination Survey (NHANES) 2013–2014

Abstract: Anabasine and anatabine are minor alkaloids in tobacco products and are precursors for tobacco-specific nitrosamines (TSNAs). The levels of these two compounds have been used to differentiate tobacco product sources, monitor compliance with smoking cessation programs, and for biomonitoring in TSNA-related studies. The concentrations of urinary anabasine and anatabine were measured in a representative sample of U.S. adults who smoked cigarettes (N = 770) during the 2013–2014 National Health and Nutrition Examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Profiling can be focused on a priori hypotheses, for example in tobacco research this can assess pathways known to be involved in carcinogenesis as hallmarks of cancer [ 1 ], or xenobiotic metabolism of carcinogens and other toxicants. For each omics type bioinformatic methods and databases are available to associate features with pathways and assess the magnitude of impacts on the pathway [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Profiling can be focused on a priori hypotheses, for example in tobacco research this can assess pathways known to be involved in carcinogenesis as hallmarks of cancer [ 1 ], or xenobiotic metabolism of carcinogens and other toxicants. For each omics type bioinformatic methods and databases are available to associate features with pathways and assess the magnitude of impacts on the pathway [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Analytic approaches have been summarized by Kaur and coworkers [ 4 ], Kim and Tagkopouos [ 3 ] and Reel and coworkers [ 2 ]. They note advantages and disadvantages for analytic tools for machine learning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minor tobacco alkaloids, anabasine and anatabine, were present in cigarettes but absent in NRT products or less than 0.6% of nicotine content in vaping products . Recent studies suggest that anabasine and anatabine can be used as biomarkers to differentiate tobacco use from the use of NRT products. , These two compounds have been used for this purpose in tobacco cessation programs and were first evaluated for application in WBE by Tscharke et al…”
Section: Introductionmentioning
confidence: 99%
“…13 Recent studies suggest that anabasine and anatabine can be used as biomarkers to differentiate tobacco use from the use of NRT products. 14,15 These two compounds have been used for this purpose in tobacco cessation programs 16 and were first evaluated for application in WBE by Tscharke et al 17 Lai et al 18 measured anabasine and anatabine in wastewater samples in Belgium and reported a stable weekly mass load pattern. More recent studies have used anabasine and anatabine to assess long-term trends of tobacco use in different Australian cities between 2012 and 2017, showing a quicker decrease of tobacco use than nicotine use.…”
Section: Introductionmentioning
confidence: 99%